ACM Symposium on Eye Tracking Research and Applications 2021
DOI: 10.1145/3448018.3458002
|View full text |Cite
|
Sign up to set email alerts
|

Synchronization of Spontaneous Eyeblink during Formula Car Driving

Abstract: Formula car racing is a highly competitive sport. Previous studies have investigated the physiological characteristics and motor behaviors of drivers; however, little is known about how they modulate their cognitive states to improve their skills. Spontaneous eyeblink is a noteworthy factor because it reflects attentional states and is important for drivers to minimize the chance of losing critical visual information. In this study, we investigated whether the blink rate, blink synchronization among laps in ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 18 publications
1
3
0
Order By: Relevance
“…There were hidden task-related spatial structures underlying the eyeblink pattern. Our analysis extrapolated findings from the known individual differences in eyeblink rate 11 , 36 ( Figures 1 F and S2 ) and eyeblink synchronicity for engagement 31 , 32 ( Figures 1 I and S4 ) and showed a correlation between short-term cognitive demand and eyeblink generation probability ( Figures 2 A and 2B). 14 , 22 These findings were valid and underlay the spatial pattern, but cast doubt 37 , 38 on the effect of the relationship between longer-term cognitive demand and eyeblink rate 19 ( Figure 1 H) in a real-world extreme sensorimotor task.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…There were hidden task-related spatial structures underlying the eyeblink pattern. Our analysis extrapolated findings from the known individual differences in eyeblink rate 11 , 36 ( Figures 1 F and S2 ) and eyeblink synchronicity for engagement 31 , 32 ( Figures 1 I and S4 ) and showed a correlation between short-term cognitive demand and eyeblink generation probability ( Figures 2 A and 2B). 14 , 22 These findings were valid and underlay the spatial pattern, but cast doubt 37 , 38 on the effect of the relationship between longer-term cognitive demand and eyeblink rate 19 ( Figure 1 H) in a real-world extreme sensorimotor task.…”
Section: Discussionsupporting
confidence: 70%
“… 31 With driving at a faster lap pace, cognitive demand and engagement in driving would increase, and a decrease in eyeblink rate and an increase in eyeblink pattern similarity were assumed. Our preliminary results 32 suggested that the relationship between lap pace and eyeblink timing pattern similarity was more robust than the relationship between lap pace and eyeblink frequency. This was replicated in the larger dataset of this study ( Figures 1 I, S4 , 1H, and S3 ).…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Blinks (0.1-0.3 s duration) also break up the visual input. Expert racing drivers that are highly reliant on high-quality input seem to tactically perform blinks at specific, less critical parts of the track (Nishizono et al, 2021). 5.3.…”
Section: Eyes On the Roadmentioning
confidence: 99%